2011
DOI: 10.2139/ssrn.1806084
|View full text |Cite
|
Sign up to set email alerts
|

Effective Affirmative Action in School Choice

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 35 publications
0
111
0
Order By: Relevance
“…Although there is a large literature in education evaluating and estimating the effects of segregation across schools on students' achievements (Hanushek, Kain, and Rivkin (2002), Guryan (2004), Card and Rothstein (2005), and others), 23 and on how to measure segregation and how to determine optimal desegregation guidelines, 24 none of these papers discusses the problem of how in practice to assign students to schools while complying with these desegregation guidelines. This is exactly what the first part of our paper does.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a large literature in education evaluating and estimating the effects of segregation across schools on students' achievements (Hanushek, Kain, and Rivkin (2002), Guryan (2004), Card and Rothstein (2005), and others), 23 and on how to measure segregation and how to determine optimal desegregation guidelines, 24 none of these papers discusses the problem of how in practice to assign students to schools while complying with these desegregation guidelines. This is exactly what the first part of our paper does.…”
Section: Resultsmentioning
confidence: 99%
“…An example showing the contrary is available from the authors. 23 We will refer the interested reader to Echenique, Fryer, and Kaufman (2006) for an illuminating account of this literature. 24 School segregation can be purely racial or, as in Echenique, Fryer and Kaufman (2006), school segregation is measured according to the spectral segregation index of Echenique and Fryer (2006) which uses the intensity of social interactions among the members of a group (see also Cutler and Glaeser (1997)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be done by allocating the places for siblings first and then the remaining seats or in reverse. Dur et al (2013) showed that the reverse approach can benefit children with siblings, and Hafalir et al (2013) showed that reserving places for a certain minority results in a better allocation for the minority than limiting the quota for the majority does. Under the latter policy, both groups (minority and majority) could be worse off.…”
Section: Operationalisation Of Policy Designsmentioning
confidence: 99%
“…These constraints usually take the form of lower or upper limits for students in particular ethnic, racial or socio-economic groups. For analysis of controlled school choice problems see, for example, Kojima (2012), Hafalir, Yenmez and Yildirim (2013) and Ehlers et al (2014). When the number of students at each school is exactly one then quotas and other limits intended to ensure diversity clearly do not apply.…”
Section: Top Trading Cyclesmentioning
confidence: 99%